Community of Soil Actinobacteria in PTPN VI Oil Palm Plantation Jambi (Sumatra, Indonesia) Based on Amplicon Sequencing of 16S rRNA Gene - Mazidah Noer Inayah; Yulin Lestari; Anja Meryandini (Bogor Agricultural University, Indonesia, 2022)
In Sumatra, Indonesia, increased oil palm production encourages land expansion for oil palm plantations. And soil Actinobacteria have a potential role in agriculture and plantations ecosystems. The use of fertilizer and herbicide affects soil microbial diversity, including Actinobacteria. This research analyzed and investigated the community composition and diversity of Actinobacteria in soils of oil palm plantations in Jambi Sumatra. Amplicon-based analysis of the 16S rRNA gene (V3-V4 hypervariable region) was used to amplify actinobacterial full-length 16S sequences. The V3-V4 actinobacterial specific 16S rRNA gene sequencing was done using Next-Generation Sequencing. This study confirmed that actinobacterial specific 16S rRNA gene primer could amplify the actinobacterial 16S rRNA gene. Frankiales dominated the community composition of soilborne Actinobacteria. The diversity and community composition of soilborne Actinobacteria were not significantly affected by the interaction between fertilization and weed treatments. Furthermore, the use of NPK fertilizer significantly affected the abundance of Kineosporiales, whose abundance increased with the increasing concentration of NPK fertilizer. The interaction between fertilization and weeding treatments in the oil palm plantations has no impact on soil Actinobacteria's community composition and diversity.